Pengaruh Pembelajaran Terintegrasi Islam Dan Sains Terhadap Hasil Belajar Siswa Kelas XI MIPA 4 - ize, ulfa; Imam Nawawi; Ira Nurmawati (JOURNAL SAINS STUDENT RESEARCH, 2025)
Abstrak. The integration of knowledge from an Islamic perspective continues to be developed by Islamic education scholars. This idea emerged as a response to the dualism or separation between religious and secular sciences, which later gave rise to a segregated education system. In Indonesia, this dichotomy is clearly reflected in the diversity of educational institutions. The idea of unifying science and Islam has long been a topic of discussion. Although the term "integration" is not always explicitly mentioned, there is an understanding of the importance of uniting knowledge and religion. This study uses a quantitative approach with a pre-experimental design in the form of a one-group pretest-posttest model. The research design applied involves the use of pretest-posttest sheets as the research instrument. Data analysis was carried out using the Wilcoxon Signed Rank Test, with prerequisite tests including normality and homogeneity tests. The results of the study are as follows: (1) there is a significant difference in the average scores between the pretest (320) and the posttest (512); (2) the Wilcoxon Signed Rank Test to determine the effect of the integration of Islam and science yielded a significance value (2-tailed) of 0.000 < 0.05, indicating that H₀ is rejected and Hₐ is accepted. This means there is a difference between the pretest and posttest scores, showing that the integration of Islam and science has an influence on the learning outcomes of Grade XI MIPA 4 students in Biology learning at MAN 2 Jember in the 2022/2023 academic year. Keywords: Dichotomy; Integration; Islam; Science